TAFSIR AHKAM TERHADAP KISAH AL-QUR’AN DALAM KITAB SYAJARATU AL-MA’ARIF KARYA ‘IZZUDDIN ABDUSSALAM - Mahfudz, Ali (STAI Al-Mujtama Pamekasan, 2024)
This article aims to analyze the tafsir ahkam (jurisprudential exegesis) of Qur'anic stories in the book Syajaratu al-Ma’arif by Izzuddin Abdussalam. The study seeks to uncover how Izzuddin Abdussalam, as a scholar of fiqhand tafsir, employs a legal approach in interpreting the stories of the Qur’an and the relevance of his interpretations in the context of Islamic law. The research method used is library research, gathering primary data from the book Syajaratu al-Ma’arif and secondary data from related literature. The analysis is conducted using Gadamer’s historical influence approach, which allows for a deeper understanding of the historical context and legal interpretation undertaken by Izzuddin Abdussalam. The research findings demonstrate that Izzuddin Abdussalam effectively combines legal knowledge with Qur’anic narratives, using these stories as a basis for formulating applicable legal principles in everyday life. Keywords: Tafsir ahkam, Qur’anic stories, Syajaratu al-Ma’arif, Izzuddin Abdussalam